2016
DOI: 10.3390/s16101667
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable Complementary Split Ring Resonator (CSRR)-Based Radio Frequency (RF) Sensor for Strain Direction and Level Detection

Abstract: In this paper, we proposed a stretchable radio frequency (RF) sensor to detect strain direction and level. The stretchable sensor is composed of two complementary split ring resonators (CSRR) with microfluidic channels. In order to achieve stretchability, liquid metal (eutectic gallium-indium, EGaIn) and Ecoflex substrate are used. Microfluidic channels are built by Ecoflex elastomer and microfluidic channel frames. A three-dimensional (3D) printer is used for fabrication of microfluidic channel frames. Two CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…The authors of [47] demonstrated a stretchable sensor based on complementary SRR with 24 MHz/% measured sensitivity. This high value came at the cost of a very low quality-factor of 4.5-4.8 and large electrical size of 2.5λ g × 3.5λ g , while the proposed sensor exhibits a high Q-factor of 226 with a very small size of 0.13λ g × 0.13λ g and a simpler design.…”
Section: Comparison Of the Reported Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [47] demonstrated a stretchable sensor based on complementary SRR with 24 MHz/% measured sensitivity. This high value came at the cost of a very low quality-factor of 4.5-4.8 and large electrical size of 2.5λ g × 3.5λ g , while the proposed sensor exhibits a high Q-factor of 226 with a very small size of 0.13λ g × 0.13λ g and a simpler design.…”
Section: Comparison Of the Reported Literaturementioning
confidence: 99%
“…This is mostly due to the fact that amplitude noise at a low signal level considerably impacts the measurements such that a perfect measurement at a fixed frequency is almost impossible [45]. In addition to displacement, rotation sensing and also stretch analysis are of great importance in detecting mechanical alterations and can be implemented using the same metamaterial-based techniques [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Elastomer substrates tend to provide flexibility and bendability, which are essential requirements for wearable devices, artificial skin and flexible touch screens. Polydimethylsiloxane (PDMS) is widely used as a flexible substrate [ 23 ]. For a detailed comparison of polymer substrates, [ 24 ] can be seen.…”
Section: Inkjet-printing Technologymentioning
confidence: 99%
“…Also, microwave structures can be readily implemented in the integrated circuits, which have become a favourable platform due to their constantly decreasing cost. As such, microwave sensors have found numerous applications including permittivity sensing [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], strain and displacement sensing [ 16 , 17 , 18 , 19 , 20 ], detection of biomolecules [ 21 ], glucose monitoring [ 22 , 23 ], dielectric spectroscopy for food quality control [ 24 , 25 ], gas sensing [ 26 , 27 , 28 ], and concentration measurements of liquid solutions [ 29 ].…”
Section: Introductionmentioning
confidence: 99%